Snow White's Characterizations in Regis Maine's Comic Snow White and The Seven Dwarfs - Ida Ayu Devi Pujayani (Jurnal Penelitian Mahasiswa Indonesia, 2023)
The characterizations of a character in a narrative can be analyzed and concluded in various ways. This study aims to find out the characterizations of the main character in the comic Snow White and The Seven Dwarfs by Regis Maine. This study presents 1) the characterizations of Snow White as the main character in the comic Snow White and The Seven Dwarfs by Regis Maine; 2) the revelation of the characterizations of Snow White in the comic Snow White and The Seven Dwarfs by Regis Maine; 3) The proofs of the characterizations of Snow White through the quotes, speech, conversations, and opinion of other characters that are written in the comic. The explanations of the action and events also support the proofs to emphasize the characterizations. Through critical reading, this study found that the comic tells Snow White in the nine characterizations which are diligent, cheerful, beautiful, brave, strong, loving, kind-hearted, shy, and polite. The characterizations of Snow White are revealed in several ways, starting from direct presentation by the narrator, direct presentation by other characters, indirect presentation through action, indirect presentation through speech, and indirect presentation through conversation